2022
DOI: 10.3390/diseases10040124
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in Bacterial Uropathogens and Their Antimicrobial Susceptibility Profile in Diabetics and Their Non-Diabetic Caregivers at a National Diabetes Management and Research Centre, Accra-Ghana

Abstract: Background: Diabetes mellitus has some damaging effects on the genitourinary system and has been found to have adverse effects on the host immune system, resulting in higher risk of infections including urinary tract infections (UTI). Incidences of UTI caused by bacteria have been increasingly reported globally and the abuse of antibiotics leading to evolving resistant strains of antibiotics is a public health challenge for the management of this condition. Information on the difference in types of bacterial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Gram-negative enteric organisms including Escherichia coli, Klebsiella species, and Proteus species, which frequently cause urinary tract infections, are typically implicated in bacterial research. 15,17 Similarly, Gramnegative pathogens were more frequently isolated than Gram-positive ones. Escherichia coli was found among the diabetic patients, with Klebsiella, Pseudomonas aeruginosa, Proteus species, Citrobacter freundii, Acinetobacter species, Enterococcus species, Staphylococcus aureus, and CoNS being the next most common bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram-negative enteric organisms including Escherichia coli, Klebsiella species, and Proteus species, which frequently cause urinary tract infections, are typically implicated in bacterial research. 15,17 Similarly, Gramnegative pathogens were more frequently isolated than Gram-positive ones. Escherichia coli was found among the diabetic patients, with Klebsiella, Pseudomonas aeruginosa, Proteus species, Citrobacter freundii, Acinetobacter species, Enterococcus species, Staphylococcus aureus, and CoNS being the next most common bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli was found to be the most often growing organism in both diabetes and non-diabetic subjects in a research that was identical to the one from India (34.92% and 29.09%). 15 A greater propensity for Escherichia coli adherence has been seen in diabetic individuals with poor glycemic control. 16 Patients with diabetes had a little greater percentage prevalence of uropathogens than nondiabetics, who had a prevalence of 36.6%; however, this difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of these antibiotics attributed to the fact that these drugs are not easily available and are relatively expensive as compared to other drugs in the study. Therefore, these drugs could be considered as therapeutic options in the empirical treatment of UTI in both diabetic and nondiabetic population [35].…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Wang et al on 271 E. coli strains isolated from urine samples (190 from diabetic and 81 from non-diabetic patients) reported a similar antimicrobial resistance profile between diabetic and non-diabetic patients, excepting a higher resistance rate to the second-and third-generation cephalosporins in the diabetic patients [44]. In addition, Owusu et al conducted a prospective cross-sectional study including 100 diagnosed diabetic patients and 100 non-diabetic individuals that showed that bacterial strains isolated from both diabetic and non-diabetic individuals were highly susceptible to most of the antibiotics tested, especially nitrofurantoin, cefuroxime, ceftriaxone, and cefotaxime [46].…”
Section: Microorganism Involved and Antibiotic Susceptibility Profilementioning
confidence: 99%